Drought controls on H2O2 accumulation, catalase (CAT) activity and CAT gene expression in wheat - Luna, Celina Mercedes (2005)
Plants co-ordinate information derived from many diverse external and internal signals to ensure appropriate control of gene expression under optimal and stress conditions. In this work, the relationships between catalase (CAT) and H2O2 during drought in wheat (Triticum aestivum L.) are studied. Drought-induced H2O2 accumulation correlated with decreases in soil water content and CO2 assimilation. Leaf H2O2 content increased even though total CAT activity doubled under severe drought conditions. Diurnal regulation of CAT1 and CAT2 mRNA abundance was apparent in all conditions and day/night CAT1 and CAT2 expression patterns were modified by mild and severe drought. The abundance of CAT1 transcripts was regulated by circadian controls that persisted in continuous darkness, while CAT2 was modulated by light. Drought decreased abundance, and modified the pattern, of CAT1 and CAT2 mRNAs. It was concluded that the complex regulation of CAT mRNA, particularly at the level of translation, allows precise control of leaf H2O2 accumulation.